Proposed corrections to the IEC 61131-3 standard - Mário de Sousa (2010)
The IEC (International Electrotechnical Commission) 61131-3 standard defines several programming languages which may be used to develop industrial control applications. These applications typically execute on industrial PLCs (Programmable Logic Controller). PLC vendors have embraced the first version of this standard [3], with each vendor adopting it at its own pace. As the standard is implemented, several deficiencies have been uncovered. In this paper deficiencies identified by the authors during the implementation of a compiler, compliant with the second version of the standard [4], are explained and analysed. Other deficiencies identified by other authors have also been aggregated and explained. For each deficiency, one or more suggestions (including changes to the formal syntax definition) are made as to how the standard could be changed in order to rectify the deficiency.